2005
DOI: 10.1007/s00467-005-1964-z
|View full text |Cite
|
Sign up to set email alerts
|

Mycophenolate mofetil therapy in frequently relapsing steroid-dependent and steroid-resistant nephrotic syndrome of childhood: current status and future directions

Abstract: Clinicians are often faced with therapeutic dilemmas and challenges while treating children with frequently relapsing steroid-dependent nephrotic syndrome (SDNS) and steroid-resistant nephrotic syndrome (SRNS). In the past, children with SDNS have been treated with long-term alternate day steroids cyclophosphamide, cyclosporine (CSA), chlorambucil, levamisole, and azathioprine. The essential aim of these therapies is to maintain remission while limiting exposure to steroids. These medications have variable eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 57 publications
3
36
0
2
Order By: Relevance
“…[14][15][16] MMF has also been proven effective in autoimmune diseases in children. [17][18][19][20] Here, we report our experience with MMF in paediatric patients with autoimmune uveitis.…”
Section: Clinical Studymentioning
confidence: 99%
See 1 more Smart Citation
“…[14][15][16] MMF has also been proven effective in autoimmune diseases in children. [17][18][19][20] Here, we report our experience with MMF in paediatric patients with autoimmune uveitis.…”
Section: Clinical Studymentioning
confidence: 99%
“…Nine of them achieved inflammation control on MMF without concomitant corticosteroids or other IMTs for a median of 15 months (range: [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. During this follow-up period, 8 out of the 9 patients experienced no uveitis relapse; 1 patient experienced one relapse that was treated with 4 weeks of topical corticosteroids.…”
Section: Treatment Outcomesmentioning
confidence: 99%
“…Numerous immunosuppressive agents have shown to be effective in a subset of SRNS patients (8,9). Cyclosporine A (CsA) is used preferentially and several studies demonstrated CsA-induced remission rates (including partial remission) of up to 70% in pediatric SRNS patients (10 -12).…”
mentioning
confidence: 99%
“…Overall, relapse rate after discontinuation of cyclosporine was 67%; and that of corticosteroids was 55%. 1,18 In recent years, mycophenolate mofetil (MMF) (brand names: CellCept), 19 originally approved by the FDA as an immunosuppressant for transplant patients, 20 has become a novel choice for primary FSGS patients who have exhausted these two frontline treatment options. MMF acts through its inhibition on the inosine monophosphate dehydrogenase, which reduces T and B lymphocyte proliferation.…”
Section: Introductionmentioning
confidence: 99%